2008
DOI: 10.1029/2007jd008568
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term memory in 1000‐year simulated temperature records

Abstract: [1] We study the appearance of long-term persistence in temperature records, obtained from the global coupled general circulation model ECHO-G for two runs, using detrended fluctuation analysis. The first run is a historical simulation for the years 1000-1990 (with greenhouse gas, solar, and volcanic forcing), while the second run is a 1000-year ''control run'' with constant external forcings. We consider daily data of all grid points as well as their biannual averages in order to suppress 2-year oscillations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 37 publications
3
72
1
Order By: Relevance
“…4 shows the DFA results of one of the random samplings with a = 0.51 and standard deviation 0.03 for each geographical area. In other words, we find that the DFA exponent that characterizes the fluctuations in the shuffled data is near 0.5, thus indicating that the Joseph phenomenon is the main effect (Mandelbrot and Wallis, 1968;Rybski et al, 2008). On the other hand, the estimated DFA exponents depicted in Fig.…”
Section: Data and Analysismentioning
confidence: 77%
See 1 more Smart Citation
“…4 shows the DFA results of one of the random samplings with a = 0.51 and standard deviation 0.03 for each geographical area. In other words, we find that the DFA exponent that characterizes the fluctuations in the shuffled data is near 0.5, thus indicating that the Joseph phenomenon is the main effect (Mandelbrot and Wallis, 1968;Rybski et al, 2008). On the other hand, the estimated DFA exponents depicted in Fig.…”
Section: Data and Analysismentioning
confidence: 77%
“…Recently, six reconstructed records of the Northern Hemisphere (NH) temperatures, analysed by Rybski et al (2006), revealed long-term persistence. Due to the long-term persistent correlations, the mean temperature variations σ (m, L) between L years (moving averages over m years) were substantially larger than for uncorrelated or short-term correlated data.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there exist many studies that investigate the long-term correlation of temperature data. Some of these studies (Koscielny- Bunde et al, 1998;Bunde et al, 2001;Govindan et al, 2003) claim that the scaling exponent is universal for the temperature data while the others Kurnaz, 2004;Pattanyús-Ábrahám et al, 2004;Kiràly and Jánosi, 2005;Bartos and Jánosi, 2006;Kiràly et al, 2006;Rybski et al, 2008) claim the opposite. Apart from temperature data, the DFA analysis has also been applied to some meteorological and climatological variables such as wind speed (Govindan and Kantz, 2004;Kavasseri and Nagarajan, 2004), relative humidity (Chen et al, 2007), cloud breaking (Ivanova and Ausloos, 1999) and NAO (North Atlantic Oscillation) index (Caldeira et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…GCM control runs (with fixed boundary conditions, i.e., with fixed atmospheric composition, solar output, and orbital parameters and without volcanism) are found to generate a macroweather regime with H ≈ −0.4 out to the extreme lowfrequency limit of the models (several millennia [ Blender et al ., 2006;Rybski et al ., 2008 ;). Since GCMs are essentially weather models with extra couplings, the name "macro weather" is appropriate.…”
Section: Climate Modeling Prediction and Anthropogenic Effectsmentioning
confidence: 99%